Fgf differentially controls cross-antagonism between cardiac and haemangioblast regulators. - Simões, F; Peterkin, T; Patient, R (Company of Biologists, 2011)
Fibroblast growth factor (Fgf) has been implicated in the control of heart size during development, although whether this is by controlling cell fate, survival or proliferation has not been clear. Here, we show that Fgf, without affecting survival or proliferation, acts during gastrulation to drive cardiac fate and restrict anterior haemangioblast fate in zebrafish embryos. The haemangioblast programme was thought to be activated before the cardiac programme and is repressive towards it, suggesting that activation by Fgf of the cardiac programme might be via suppression of the haemangioblast programme. However, we show that the cardiac regulator nkx2.5 can also repress the haemangioblast programme and, furthermore, that cardiac specification still requires Fgf signalling even when haemangioblast regulators are independently suppressed. We further show that nkx2.5 and the cloche candidate gene lycat are expressed during gastrulation and regulated by Fgf, and that nkx2.5 overexpression, together with loss of the lycat targets etsrp and scl can stably induce expansion of the heart. We conclude that Fgf controls cardiac and haemangioblast fates by the simultaneous regulation of haemangioblast and cardiac regulators. We propose that elevation of Fgf signalling in the anterior haemangioblast territory could have led to its recruitment into the heart field during evolution, increasing the size of the heart.